Performance characteristics of hot mix asphalt with recycled materials - Lee, Zhen Hao. (2009)
Recycled Concrete Aggregate (RCA) was used as a partial replacement of Indonesian granite aggregates in LTA’s W3B mix to evaluate it’s feasibility in hot mix asphalt (HMA) application.